2021
DOI: 10.1126/science.abe0874
|View full text |Cite
|
Sign up to set email alerts
|

Tool use and language share syntactic processes and neural patterns in the basal ganglia

Abstract: Common basis for language and tool use Tool use and language are hallmarks of human evolution. Because of the similarity between the motor processes for tool use and those supporting language, it has been hypothesized that syntax and tool use may share brain resources. Using functional magnetic resonance imaging and multivariate pattern analysis, Thibault et al . found that small portions of the basal ganglia in the human brain act as common neural substrates for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 74 publications
2
41
0
Order By: Relevance
“…Finally, the finding of common neuro-functional resources between semantics and tool use predicts potential reciprocal impact of one function over the other at the behavioral level 3,39 . Coherently, the use of novel tools that received a label, which may have sharpened their semantic representation, is facilitated in comparison to unlabeled tools 40 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, the finding of common neuro-functional resources between semantics and tool use predicts potential reciprocal impact of one function over the other at the behavioral level 3,39 . Coherently, the use of novel tools that received a label, which may have sharpened their semantic representation, is facilitated in comparison to unlabeled tools 40 .…”
Section: Discussionmentioning
confidence: 99%
“…This specificity might depend on the degree of similarity between the computations performed by given neural structures (i.e. IFG and OTC for conceptual processing and BG for hierarchical processing 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent evidence also suggests that body representation and cognitive skills are directly linked. It was recently shown that integrating an external object as a body part and embedding its functional structure in the motor program can selectively improve syntactic performance in language in adults [ 33 ]. It appears essential to promote efficient body representation in children during early development.…”
Section: Introductionmentioning
confidence: 99%